Exploring Cultural Stereotypes In Aladdin (1992) Movie By Disney - Yayu Sri Rahayu Kobandaha; Magdalena Baga; Farid Muhamad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the cultural stereotypes presented in Disney’s Aladdin (1992), focusing on how the film represents Middle Eastern culture through characters, plot, setting, and themes. Using the theoretical framework of Stuart Hall’s representation theory, Richard Dyer’s concept of stereotypes, and Edward Said’s Orientalism, this research applies a qualitative descriptive method through film text analysis. The findings reveal that Aladdin contains strong elements of Orientalism, depicting Arab culture as exotic, irrational, and inferior compared to Western civilization. Characters such as Jafar, the Sultan, and even Aladdin himself are shaped through stereotypical lenses that reinforce Western cultural dominance. The film’s narrative and visual elements, from costume design, language, and setting to the theme of freedom versus control, perpetuate Western superiority while diminishing the cultural complexity of the Middle East. This study concludes that Aladdin not only entertains but also functions as a vehicle of cultural misrepresentation, shaping global perceptions of Arab identity.